Entrepreneurial Empowerment of Housewives Through Training in Making Various Processed Freshwater Fish in Cilamo Village, Girimukti Village, Garut District - Aliman; Aghni Aulia Aziz (RECORD: Journal of Loyality and Community Development, 2024)
Girimukti Village is one of the villages in Cibatu District in Garut Regency, West Java Province. MSME actors in Girimukti Village are still low, while the potential for development is both in terms of natural resources and human resources. From the aspect of human resources that still have the potential and opportunities to be utilized in the MSME program are housewives who have time so that they can be directed and fostered to be more productive. Basically, the purpose of carrying out Community Service is to be able to provide new ideas about entrepreneurship for housewives and motivate housewives to want to be entrepreneurs. The target to be achieved is that the community becomes creative and can make various processed products made from freshwater fish to be used as one of the ideas to be used as an opportunity for entrepreneurship so that it can increase family income and be able to analyze the feasibility of entrepreneurship in making snacks.